Transport company safety climate - the impact on truck driver behaviour and crash involvement - Sullman, Mark J. M.; Stephens, A. N.; Pajo K. (Taylor & Francis, 2017)
Objective: The present study investigated the relationships between safety climate and driving behavior and crash involvement. Methods: A total of 339 company-employed truck drivers completed a questionnaire that measured their perceptions of safety climate, crash record, speed choice, and aberrant driving behaviors (errors, lapses, and violations). Results: Although there was no direct relationship between the drivers' perceptions of safety climate and crash involvement, safety climate was a significant predictor of engagement in risky driving behaviors, which were in turn predictive of crash involvement. Conclusions: This research shows that safety climate may offer an important starting point for interventions aimed at reducing risky driving behavior and thus fewer vehicle collisions.
Keywords: Safety climate; trucks; crash involvement; aberrant driving behavior; DBQ